Structure of Escherichia coli cytochrome bd-II type oxidase with bound aurachin D - Antonia Grauel (Nature Portfolio, 2021)
Terminal bd oxidases endow bacterial pathogens with resistance to cellular stressors. The authors report the structure of E. coli bd-II type oxidase with the bound inhibitor aurachin D, providing a structural basis for the design of specifically binding antibiotics.